Nuclear energy in Hungary - Katona, Tamás János (Hungarian Geographical Bulletin, 2009)
Options for the development of electric power generation industry in Hungary are considered. The Paks Nuclear Power Plant Ltd. is a stable element of the energy system of the country. Its significance in power supply is demonstrated and preparatory works for new nuclear projects are presented. The feasibility of construction of a new plant is outlined. Basic aspects of preparatory work and its results are presented in the paper.